Growth, longevity, and juvenile recruitment of the white shrimp Litopenaeus schmitti (Burkenroad, 1936) (Decapoda: Penaeoidea) in southeastern Brazil - Miazaki, Lizandra Fernandes [UNESP] (2018)
Litopenaeus schmitti is one of the most commercially exploited penaeids on the southeastern and southern Atlantic coast of Brazil. Information about juvenile recruitment and growth patterns of individuals is important for management programs. The present study estimated the growth parameters, longevity, and recruitment of L. schmitti in the region of Ubatuba, São Paulo State. The growth parameters of individuals were estimated by the Bertalanffy growth model, and longevity was estimated with the inverted Bertalanffy equation. The growth parameters were, for females and males respectively: CL∞ = 53.10 mm and 43.23 mm, k = 1.82 year-1 and 2.19 years-1, t0= 1.10 and 0.69. Longevity was calculated to be 2.27 years for females and 2.10 years for males. Juvenile recruitment occurred seasonally from December to April during the first year of sampling and from November to May in the second year. Although the large peak in juveniles seen in March 2007 in the estuarine regions coincided with the closed season, the reopening of the fishery in June may promote the capture of large numbers of newly grown adults who have not yet reproduced.